Penyuluhan Kesehatan Tentang Personal Hygiene dan Pencegahan Demam Berdarah di Panti Asuhan Nurul Haq Madania Bantul - Antok Nurwidi Antara; Novi Istanti; Patria Asda (Lembaga Pengembangan Kinerja Dosen, 2024)
Dengue Hemorrhagic Fever (DHF) is an infectious disease that can be prevented by creating a clean and healthy surrounding environment and our behavior or personal hygiene to prevent mosquito breeding. Teenagers are the nation's next generation who need to be given knowledge about dengue prevention. The aim of this community service is to increase the knowledge of Nurul Haq Madania Bantul orphanage students about personal hygiene and dengue prevention. The method of this activity is by means of lecture and question and answer. The number of orphanage students who took part in this activity was 28 people, but there were 2 people who did not participate until the end. The results obtain that this community service activity is a form of applying health knowledge from the community service team and has been able to increase the knowledge of Nur Madania Orphanage students about dengue fever prevention and personal hygiene.